Vibrational study and force field of the citric acid dimer based on the SQM methodology - Brandán, Silvia Antonia (2011)
We have carried out a structural and vibrational theoretical study for the citric acid dimer. The Density Functional Theory (DFT) method with the B3LYP/6-31G() and B3LYP/6-311++ G methods have been used to study its structure and vibrational properties. Then, in order to get a good assignment of the IR and Raman spectra in solid phase of dimer, the best fit possible between the calculated and recorded frequencies was carry out and the force fields were scaled using the Scaled Quantum Mechanic Force Field (SQMFF) methodology. An assignment of the observed spectral features is proposed. A band of medium intensity at 1242 cm - 1 together with a group of weak bands, previously not assigned to the monomer, was in this case assigned to the dimer. Furthermore, the analysis of the Natural Bond Orbitals (NBOs) and the topological properties of electronic charge density by employing Bader's Atoms in Molecules theory (AIM) for the dimer were carried out to study the charge transference interactions of the compound.